Conexiones culturales entre Roma y Barcino: una visión a través de la iconografía de las lucernas - de Frutos Manzanares, Laia (Collectanea Philologica, 2022)
Roman lamps were one of the few daily-use objects that could have been usually decorated, thanks to the free space they had on their central discuses, offering a wide variety of figurative motifs. Such richness of elements and details permits to study their iconography as a reflection of Roman imaginary and daily life. About Iberian Peninsula, it is possible to observe how the Roman culture and traditions arrived and started to be introduced in this area through the analysis of their decorations. This paper will regard the specific situation of ancient Barcino (Barcelona), a paradigmatic case in respect of the application of that kind of analysis in order to better understand the Roman society that lived there. *Este capítulo se enmarca dentro de la propia tesis en curso, desarrollada gracias a la ayuda PRE2018-084077 financiada por MCIN/AEI/10.13039/501100011033 y FSE “El FSE invierte en tu futuro”. Se enmarca además dentro del grupo CEIPAC (Centro para el Estudio de la Interdependencia Provincial en la Antigüedad Clásica) de la Universidad de Barcelona, y de UBICS (Universitat de Barcelona Institute of Complex Systems). Financiada también por los proyectos: Relaciones Interprovinciales en el Imperio Romano. Producción y comercio de alimentos hispanos (Provinciae Baetica et Tarraconensis) (HAR2017-85635-P) 2017–2020; Centro para el Estudio de la Interdependencia Provincial en la Antigüedad Clásica (CEIPAC) (2017 SGR 512). 2017–2020; Projecte de Recerca Quadriennal 2018–2021 GENCAT Exp.27-CLT009|18|00045: “Dinàmiques socioeconòmiques del món rural romà: formes de l’hàbitat i cultura material al litoral central català” – Projecte Cella Vinaria- de la Universitat de Barcelona. 2018–2021”.